Composite oxide catalyst as well as preparation method and application thereof

Through the composite oxide catalyst that synergistically interacts with the Fe-based catalyst and the CuZr-based catalyst, the problem of insufficient activity and selectivity of the Fe-based catalyst in the preparation of ethanol by hydrogenation of carbon dioxide is solved, and high activity and high selectivity of ethanol preparation is achieved, which improves economic benefits.

CN119524859AActive Publication Date: 2025-02-28SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411698430.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the prior art, Fe-based catalysts have problems of insufficient activity and selectivity in the preparation of ethanol by hydrogenation of carbon dioxide, which is difficult to meet the needs of industrial production.

Method used

The composite oxide catalyst that synergizes with the Fe-based catalyst and the CuZr-based catalyst is used to improve the activity of the catalyst and the ethanol selectivity by adjusting the composition and preparation method of the catalyst.

Benefits of technology

The effect of high activity and high ethanol selectivity in carbon dioxide hydrogenation reaction is achieved, and high purity ethanol products can be obtained, reducing separation costs and improving economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a composite oxide catalyst and a preparation method and application thereof. The composite oxide catalyst comprises the following raw materials: a Fe-based catalyst, a CuZr-based catalyst and a first carrier, on the basis of the total mass of the raw materials of the composite oxide catalyst, the content of the Fe-based catalyst is 20wt%-80wt%, the content of the CuZr-based catalyst is 15wt%-79wt%, and the content of the first carrier is 1wt%-5wt%. According to the composite oxide catalyst disclosed by the invention, the Fe-based catalyst and the CuZr-based catalyst have a synergistic effect, so that the catalyst shows high activity in a reaction for preparing ethanol through carbon dioxide hydrogenation, and also shows high ethanol selectivity under the condition of relatively high conversion rate, and a high-purity single ethanol product can be obtained; the separation cost can be greatly reduced, the economic benefit is improved, and the method has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a composite oxide catalyst and a preparation method and application thereof. Background Art

[0002] As social development continues to increase the demand for energy and resources, fossil fuels such as coal, natural gas, and oil are being consumed and large amounts of carbon dioxide are released into the air, causing a series of natural and social problems.

[0003] Through catalytic carbon dioxide hydrogenation, carbon dioxide can be converted into high-value-added chemicals such as methanol, ethanol, urea, carbonates, etc. The current market price of methanol is 2,525 yuan / ton, and the price of ethanol is 5,950 yuan / ton. Obviously, ethanol has a higher value than methanol. In the existing technology, there are three main methods for industrial ethanol production: 1. hydration method; 2. biological fermentation method; 3. direct catalytic synthesis gas (CO + H2) method. Hydration method and biological fermentation method are relatively expensive and have more side reactions. Direct synthesis gas catalytic method can effectively utilize coal resources, but still has problems such as more side reactions and low product selectivity. Since the carbon dioxide hydrogenation reaction requires more hydrogen, CC coupling is more difficult to occur during the surface reaction process compared to synthesis gas, and it is more likely to produce low-carbon number products and oxygen-containing products. It can effectively increase the ethanol yield and has great potential as an emerging method for preparing ethanol.

[0004] The current focus in the hydrogenation of CO2 to ethanol is on developing catalysts with high activity, selectivity, and stability. Based on literature reports, syngas-to-ethanol catalysts are primarily classified into three categories: 1. Precious metal catalysts, primarily Rh-, Pd-, and Au-based catalysts. Precious metals are typically supported on supports with oxygen vacancies to compensate for their poor ability to activate CO2. Typical patents include CN202110440016.4, CN201910424660.5, CN201811355101.5, and CN201610990095.5, and references include Angew Chem Int Ed, 63, 2024, e20246761; Angew Chem Int Ed, 61, 2022, e202210991. However, precious metal catalysts are prohibitively expensive, leading to high preparation costs. Supported catalysts have low metal content, and while selectivity for ethanol can approach 100%, conversion rates are low, making them unsuitable for large-scale production. (2) Modified Cu-based catalysts: The ethanol synthesis process involves activation and dissociation of carbon dioxide, and coupling of surface carbon species. Modification of Cu-based catalysts by adding alkali metals or other metals can enhance carbon-carbon coupling, converting methanol to ethanol. Typical patents include CN202111180718.X. However, the alcohol distribution of modified Cu-based catalysts is still relatively broad, making it difficult to obtain high-purity ethanol. (3) Modified Co and Fe-based catalysts: By adjusting the additive and active phase, catalysts with high activity and high ethanol selectivity can be obtained. Typical patents include CN201810137781.7 and references such as Angew Chem Int Ed, 135, 2023, e202311786; Angew Chem Int Ed, 57, 2018, 6104. However, the proportion of ethanol in alcohols of modified Co or Fe-based catalysts is often difficult to exceed 80%.

[0005] Currently, Fe-based non-precious metal catalysts have demonstrated good performance in the hydrogenation of CO2 to ethanol. Due to the low price, abundant reserves, and readily available availability of the active metallic component, Fe, and its high catalytic activity, Fe-based catalysts are considered promising ethanol catalysts for industrial applications. However, similar to other non-precious metal catalysts, Fe-based catalysts exhibit low selectivity and yield for ethanol. Improving the activity and selectivity of CO2 hydrogenation to ethanol through the rational design of Fe-based catalysts remains a major challenge. Summary of the Invention

[0006] In view of the shortcomings of the prior art described above, the present invention provides a composite oxide catalyst, a preparation method, and uses thereof. The synergistic effect of the Fe-based catalyst and the CuZr-based catalyst in the composite oxide catalyst of the present invention enables the catalyst to exhibit high activity in ethanol synthesis reactions, high ethanol selectivity at high conversion rates, and the ability to produce a single, high-purity ethanol product, significantly reducing separation costs and improving economic efficiency.

[0007] To achieve the above objectives and other related objectives, the present invention provides a composite oxide catalyst in a first aspect.

[0008] The raw materials of the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst and a first carrier; based on the total mass of the raw materials of the composite oxide catalyst, the content of the Fe-based catalyst is 20-80wt%, the content of the CuZr-based catalyst is 15-79wt%, and the content of the first carrier is 1-5wt%.

[0009] For example, the content of the Fe-based catalyst may be 20-24 wt%, 24-35 wt%, 35-40 wt%, 40-48 wt%, 48-50 wt%, 50-55 wt%, 55-67 wt%, 67-75 wt%, or 75-80 wt%.

[0010] For example, the content of the CuZr-based catalyst may be 15-20 wt%, 20-23.6 wt%, 23.6-30 wt%, 30-41 wt%, 41-49 wt%, 49-50 wt%, 50-55 wt%, 55-62 wt%, 62-70 wt%, or 70-79 wt%.

[0011] For example, the content of the first carrier may be 1-2 wt%, 2-3 wt%, 3-4 wt%, or 4-5 wt%.

[0012] Preferably, the content of the Fe-based catalyst is 24 to 75 wt%.

[0013] Preferably, the content of the CuZr-based catalyst is 23.6-62 wt%.

[0014] Preferably, the first carrier is selected from one or more of SiO2, TiO2, and Al2O.

[0015] More preferably, the first carrier is selected from one or more of gaseous SiO2, gaseous Al2O3, gaseous TiO2, liquid silica sol, TiO2 aerosol, and Al2O3 aerosol.

[0016] Preferably, the Fe-based catalyst includes Fe oxide and other oxides, and the content of the Fe oxide is 15wt% to 75wt% based on the mass of the Fe-based catalyst, and the content of the other oxides is 25wt% to 85wt%. The other oxides include a first metal oxide, and the first metal is selected from one or more of alkali metals, alkaline earth metals, transition metals, rare earth metals and Group IIIA metals.

[0017] For example, the content of the Fe oxide may be 15 wt% to 15.8 wt%, 15.8 wt% to 25 wt%, 25 wt% to 30.5 wt%, 30.5 wt% to 37.6 wt%, 37.6 wt% to 48 wt%, 48 wt% to 55 wt%, 55 wt% to 65 wt%, or 65 wt% to 75 wt%.

[0018] As described, the content of other oxides can be 25wt% to 29wt%, 29wt% to 41wt%, 41wt% to 51.2wt%, 51.2wt% to 62.4wt%, 62.4wt% to 69.5wt%, 69.5wt% to 75wt%, 75wt% to 84.2wt%, or 84.2wt% to 85wt%.

[0019] More preferably, the content of the Fe oxide is 15.8 wt% to 71 wt%.

[0020] More preferably, the content of the other oxides is 29 wt% to 84.2 wt%.

[0021] More preferably, the Fe oxide is Fe3O4.

[0022] More preferably, the other oxides further include a second carrier, and the second carrier is selected from one or more of SiO2, TiO2, and Al2O3.

[0023] More preferably, the alkaline earth metal is selected from one or more of Mg, Ca and Ba.

[0024] More preferably, the transition metal is selected from one or more of Mn, Co, Zr, Cu and Zn.

[0025] More preferably, the rare earth metal is selected from one or both of La and Ce.

[0026] More preferably, and / or, the Group IIIA metal is selected from one or both of Al and In.

[0027] Preferably, the CuZr-based catalyst includes CuZr oxide and a second metal oxide. Based on the mass of the CuZr-based catalyst, the content of the CuZr oxide is 20wt% to 85wt%, the content of the second metal oxide is 15wt% to 80wt%, and the second metal is selected from one or more of Zn, Al, Mg, and Mn.

[0028] For example, the content of CuZr oxide may be 20wt% to 30wt%, 30wt% to 36wt%, 36wt% to 45wt%, 45wt% to 55wt%, 55wt% to 61.4wt%, 61.4wt% to 67.9wt%, 67.9wt% to 75wt%, 75wt% to 81wt%, or 81wt% to 85wt%.

[0029] For example, the content of the second metal oxide may be 15wt% to 19wt%, 19wt% to 25wt%, 25wt% to 32.1wt%, 32.1wt% to 38.6wt%, 38.6wt% to 45wt%, 45wt% to 55wt%, 55wt% to 64wt%, 64wt% to 70wt%, or 70wt% to 80wt%.

[0030] More preferably, the content of the CuZr oxide is 20.2 wt% to 81 wt%.

[0031] More preferably, the content of the second metal oxide is 19 wt% to 79.8 wt%,

[0032] More preferably, the molar ratio of Cu to Zr in the CuZr oxide is (5-20): 1. For example, the molar ratio of Cu to Zr in the CuZr oxide may be (5-6): 1, (6-10): 1, (10-15): 1, or (15-20): 1.

[0033] Furthermore, the molar ratio of Cu to Zr in the CuZr oxide is (6-20):1.

[0034] The second aspect of the present invention discloses a method for preparing the composite oxide catalyst as described above, the preparation method comprising the following steps:

[0035] a1) mixing the first support, the Fe-based catalyst and the CuZr-based catalyst to obtain a solid mixture;

[0036] a2) calcining the solid mixture to obtain the composite oxide catalyst.

[0037] Preferably, in step a2), the calcination temperature is 200-500°C. For example, the calcination temperature can be 200-250°C, 250-300°C, 300-350°C, 350-400°C, 400-450°C, or 450-500°C.

[0038] Preferably, in step a2), the calcination time is 2 to 10 hours. For example, the calcination time can be 2 to 3 hours, 3 to 4 hours, 4 to 5 hours, 5 to 6 hours, 6 to 7 hours, 7 to 8 hours, 8 to 9 hours, or 9 to 10 hours.

[0039] Preferably, the preparation method of the Fe-based catalyst comprises:

[0040] b1) mixing the Fe oxide and a soluble salt of the first metal oxide other than an alkali metal and dissolving them in water to obtain a solution B;

[0041] b2) dissolving the precipitant in water to obtain solution C;

[0042] b3) adding the solution B and the solution C simultaneously dropwise into water for co-precipitation until no more precipitation is produced;

[0043] b4) After the coprecipitation is completed, aging is performed to obtain solution D;

[0044] b5) subjecting the solution D to solid-liquid separation, washing, drying and calcining the solid product obtained by the solid-liquid separation to obtain the alkali metal-free Fe-based catalyst.

[0045] More preferably, in the step b3), a second carrier is further dispersed in the mother liquor.

[0046] More preferably, the step b5) further includes impregnation, wherein the impregnation solution is an aqueous solution of a soluble salt of the alkali metal, and the operation of step b5) is repeated after impregnation, wherein the concentration of the aqueous solution of the soluble salt of the alkali metal is 0.1 to 5 mol / L.

[0047] More preferably, in step b1), the molar concentration of solution B is 0.1-5 mol / L. For example, the molar concentration of solution B can be 0.1-0.5 mol / L, 0.5-1 mol / L, 1-2 mol / L, 2-3 mol / L, 3-4 mol / L, or 4-5 mol / L.

[0048] More preferably, in step b1), the soluble salt is selected from one or more of chloride, nitrate, sulfate, carbonate or acetate.

[0049] More preferably, in step b2), the concentration of the solution C is 0.1-5 mol / L. For example, the molar concentration of the solution C can be 0.1-0.2 mol / L, 0.2-1 mol / L, 1-2 mol / L, 2-3 mol / L, 3-4 mol / L, or 4-5 mol / L.

[0050] More preferably, in step b2), the precipitant is selected from one or more of Na2CO3, K2CO3, (NH4)2CO3, NaOH, KOH and NH3·H2O.

[0051] More preferably, in step b3), the mother liquor is water.

[0052] More preferably, in step b3), the coprecipitation temperature is 30-100° C. For example, the coprecipitation temperature can be 30-40° C., 40-50° C., 50-60° C., 60-70° C., 70-80° C., or 80-100° C.

[0053] More preferably, in step b3), the pH of the mother liquor during the coprecipitation process is 7 to 12. For example, the pH of the mother liquor during the coprecipitation process can be 7 to 7.5, 7.5 to 8.5, 8.5 to 9.5, 9.5 to 10, 10 to 11, or 11 to 12.

[0054] Furthermore, in the step b3), the solution B and the solution C are dripped into the water in parallel, and the dripping speed is controlled so that the pH of the mother liquor is maintained between 7 and 12 during the coprecipitation process.

[0055] More preferably, in step b4), the aging temperature is 30-100° C. For example, the aging temperature can be 30-40° C., 40-50° C., 50-60° C., 60-70° C., 70-80° C., or 80-100° C.

[0056] More preferably, in step b4), the aging time is 2 to 48 hours. For example, the aging time can be 2 to 4 hours, 4 to 10 hours, 10 to 12 hours, 12 to 18 hours, 18 to 24 hours, 24 to 30 hours, 30 to 36 hours, 36 to 42 hours, or 42 to 48 hours.

[0057] More preferably, in step b5), the drying temperature is 100-150°C. For example, the drying temperature can be 100-110°C, 110-120°C, 120-130°C, 130-140°C, or 140-150°C.

[0058] More preferably, in step b5), the drying time is 6 to 24 hours, for example, the drying time can be 6 to 12 hours, 12 to 18 hours, or 18 to 24 hours.

[0059] More preferably, in step b5), the calcination temperature is 300-600°C. For example, the calcination temperature can be 300-350°C, 350-400°C, 400-450°C, 450-500°C, 500-550°C, or 550-600°C.

[0060] More preferably, in step b5), the calcination time is 2 to 24 hours, for example, the calcination time can be 2 to 4 hours, 4 to 8 hours, 8 to 10 hours, 10 to 12 hours, 12 to 18 hours, or 18 to 24 hours.

[0061] Preferably, the preparation method of the CuZr-based catalyst comprises the following steps:

[0062] c1) mixing the CuZr oxide and the soluble salt of the second metal oxide and dissolving them in water to obtain a solution E;

[0063] c2) dissolving the precipitant in water to obtain solution F;

[0064] c3) adding the solution F and the solution E simultaneously dropwise into the mother liquor for co-precipitation until no more precipitation is produced;

[0065] c4) after the coprecipitation is completed, aging is performed to obtain solution G;

[0066] c5) subjecting the solution G to solid-liquid separation, washing, drying and calcining the obtained solid product to obtain the CuZr-based catalyst.

[0067] More preferably, in step c1), the molar concentration of the solution E is 0.1-5 mol / L. For example, the molar concentration of the solution E can be 0.1-0.5 mol / L, 0.5-1 mol / L, 1-2 mol / L, 2-3 mol / L, 3-4 mol / L, or 4-5 mol / L.

[0068] More preferably, in step c1), the soluble salt is selected from one or more of chloride, nitrate, sulfate, carbonate or acetate.

[0069] More preferably, in step c2), the concentration of the solution E is 0.1-5 mol / L. For example, the molar concentration of the solution F can be 0.1-0.2 mol / L, 0.2-1 mol / L, 1-2 mol / L, 2-3 mol / L, 3-4 mol / L, or 4-5 mol / L.

[0070] More preferably, in step c2), the precipitant is selected from one or more of Na2CO3, K2CO3, (NH4)2CO3, NaOH, KOH and NH3·H2O.

[0071] More preferably, in step c3), the mother liquor is water.

[0072] More preferably, in step c3), the coprecipitation temperature is 30-100° C. For example, the coprecipitation temperature can be 30-40° C., 40-50° C., 50-60° C., 60-70° C., 70-80° C., or 80-100° C.

[0073] More preferably, in step c3), the pH of the mother liquor during the coprecipitation process is 7 to 12. For example, the pH of the mother liquor during the coprecipitation process can be 7 to 7.5, 7.5 to 8.5, 8.5 to 9.5, 9.5 to 10, 10 to 11, or 11 to 12.

[0074] Furthermore, in the step c3), the solution E and the solution F are dripped into the water in parallel, and the dripping speed is controlled so that the pH of the mother liquor is maintained between 7 and 12 during the coprecipitation process.

[0075] More preferably, in step c4), the aging temperature is 30-100° C. For example, the aging temperature can be 30-40° C., 40-50° C., 50-60° C., 60-70° C., 70-80° C., or 80-100° C.

[0076] More preferably, in step c4), the aging time is 2 to 48 hours. For example, the aging time can be 2 to 4 hours, 4 to 10 hours, 10 to 12 hours, 12 to 18 hours, 18 to 24 hours, 24 to 30 hours, 30 to 36 hours, 36 to 42 hours, or 42 to 48 hours.

[0077] More preferably, in step c5), the drying temperature is 100-150°C. For example, the drying temperature can be 100-110°C, 110-120°C, 120-130°C, 130-140°C, or 140-150°C.

[0078] More preferably, in step c5), the drying time is 6 to 24 hours, for example, the drying time can be 6 to 12 hours, 12 to 18 hours, or 18 to 24 hours.

[0079] More preferably, in step c5), the calcination temperature is 300-600°C. For example, the calcination temperature can be 300-350°C, 350-400°C, 400-450°C, 450-500°C, 500-550°C, or 550-600°C.

[0080] More preferably, in step c5), the calcination time is 2 to 24 hours, for example, the calcination time can be 2 to 4 hours, 4 to 8 hours, 8 to 10 hours, 10 to 12 hours, 12 to 18 hours, or 18 to 24 hours.

[0081] The third aspect of the present application discloses a use of the above-mentioned composite oxide catalyst in the preparation of ethanol by hydrogenation of carbon dioxide. Before the composite oxide catalyst is used for the preparation of ethanol by hydrogenation of carbon dioxide, the catalyst is first subjected to reduction treatment and carbonization treatment in sequence.

[0082] More preferably, the gas used in the reduction treatment is selected from one or more of H2, CO, synthesis gas and inert gas.

[0083] More preferably, the temperature of the reduction treatment is 200-500° C. For example, the temperature of the reduction treatment may be 200-250° C., 250-300° C., 300-350° C., 350-400° C., 400-450° C., or 450-500° C.

[0084] More preferably, the reduction treatment time is 2 to 48 hours. For example, the reduction treatment time can be 2 to 4 hours, 4 to 10 hours, 10 to 12 hours, 12 to 18 hours, 18 to 24 hours, 24 to 30 hours, 30 to 36 hours, 36 to 42 hours, or 42 to 48 hours.

[0085] More preferably, the space velocity of the reduction treatment is 1000 to 30000 h -1 As described, the space velocity of the reduction treatment can be 1000h -1 ~2000h -1 , 2000h -1 ~6000h -1 , 6000h -1 ~8000h -1 , 8000h -1 ~10000h -1 、10000h -1 ~20000h -1 、20000h -1 ~30,000h -1 .

[0086] More preferably, the gas used in the carbonization treatment is selected from one or more of CO, synthesis gas and inert gas.

[0087] More preferably, the space velocity of the carbonization treatment is 1000 to 30000 h-1. For example, the space velocity of the carbonization treatment can be 1000 h-1. -1 ~2000h -1, 2000h -1 ~6000h -1 , 6000h -1 ~8000h -1 , 8000h -1 ~10000h -1 、10000h -1 ~20000h -1 、20000h -1 ~30,000h -1 .

[0088] More preferably, the temperature of the carbonization treatment is 200-400°C. For example, the temperature of the carbonization treatment can be 200-250°C, 250-300°C, 300-350°C, or 350-400°C.

[0089] More preferably, the carbonization treatment time is 5 to 48 hours. For example, the carbonization treatment time can be 5 to 10 hours, 10 to 12 hours, 12 to 18 hours, 18 to 24 hours, 24 to 30 hours, 30 to 36 hours, 36 to 42 hours, or 42 to 48 hours.

[0090] The fourth aspect of the present invention discloses a method for preparing ethanol using the composite oxide catalyst as described above, wherein carbon dioxide and hydrogen react under the catalytic action of the composite oxide catalyst to prepare ethanol.

[0091] Preferably, the volume ratio of H2 to CO2 is (0.5-5):1. For example, the volume ratio of H2 to CO2 in the gas can be (0.5-1):1, (1-2):1, (2-3):1, (3-4):1, or (4-5):1.

[0092] More preferably, the volume ratio of H2 to CO2 is (2-5):1.

[0093] Preferably, the composite oxide catalyst is pressed into crushed tablets and then loaded into a fixed bed reactor for reaction.

[0094] More preferably, the reaction temperature is 200-400°C. For example, the reaction temperature can be 200-260°C, 260-300°C, 300-350°C, or 350-400°C.

[0095] More preferably, the reaction space velocity is 1000 to 20000 h -1 The space velocity of the reaction can be 1000~2000h -1 2000~3000h -1 3000~6000h -1 3000~6000h -1, 6000~10000h -1 10000~15000h -1 15000~20000h -1 .

[0096] More preferably, the reaction pressure is 2-10 MPa. For example, the reaction pressure can be 2-3 MPa, 3-4 MPa, 4-5 MPa, 5-6 MPa, 6-7 MPa, 7-8 MPa, 8-9 MPa, or 9-10 MPa.

[0097] Compared with the prior art, the present invention has the following beneficial effects:

[0098] (1) The synergistic effect of the Fe-based catalyst and the CuZr-based catalyst in the composite oxide catalyst described in the present application enables the catalyst to exhibit high activity in the ethanol synthesis reaction. Under the condition of high conversion rate, it also exhibits high ethanol selectivity, and can obtain a high-purity single ethanol product, which can greatly reduce the separation cost and improve economic benefits.

[0099] (2) The composite oxide catalyst of the present invention has good preparation repeatability. The raw material price of the composite oxide catalyst of the present invention is low, the preparation method is simple and easy to control, and it is easy to repeat the preparation to obtain products with the same quality and performance, thereby meeting the needs of large-scale stable industrial production and effectively avoiding the problem that the preparation method of traditional catalysts is too complicated and difficult to replicate, thereby failing to effectively control the stability of the quality of the catalyst.

[0100] (3) The composite oxide catalyst of the present invention has good performance repeatability. The composite oxide catalyst of the present invention can be used continuously for a long time to obtain the same good catalytic effect, reducing the time and manpower and material costs required for continuous replacement of catalysts in industrial continuous large-scale production. DETAILED DESCRIPTION

[0101] The following describes the implementation of the present invention through specific embodiments. People skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0102] Before further describing the specific embodiments of the present invention, it should be understood that the scope of the present invention is not limited to the specific embodiments described below. It should also be understood that the terminology used in the examples is intended to describe specific embodiments and is not intended to limit the scope of the present invention. The experimental procedures in the following examples, where specific conditions are not specified, were generally performed under conventional conditions or according to the conditions recommended by the respective manufacturers.

[0103] When the embodiments provide numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the understanding of the prior art by those skilled in the art and the description of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention may also be used to implement the present invention.

[0104] The reaction results of the catalyst described in the examples of this application were obtained by the following method:

[0105] 1) Analyze the types and contents of various components in the product using gas chromatography (Agilent 8860);

[0106] 2) The CO2 conversion rate is calculated based on the number of carbon atoms. The calculation formula is as follows:

[0107]

[0108] Of which CO2 inlet and CO2 outlet Represent the number of moles of CO2 entering / out of the reaction system respectively.

[0109] 3) The formula for calculating carbon monoxide selectivity is:

[0110]

[0111] Among them, CO outle Represents the number of moles of CO flowing out of the reaction tube.

[0112] 4) Methanol, ethanol and C 3+ The alcohol selectivity calculation formula (3) is shown below. 3+ Alcohols are alcohols having 3 or more carbon atoms.

[0113]

[0114] Among them, S i Refers to the selectivity of a certain type of alcohol product i (i = methanol, ethanol, propanol), N i Refers to the molar amount of a certain type of alcohol product i, n i Refers to the carbon number of a certain type of alcohol product i (for example, n=1 for methanol, n=2 for ethanol, n=3 for propanol, and so on).

[0115] The content of each oxide in the Fe-based catalyst and CuZr-based catalyst in the following examples of this application is obtained by calculating the amount of each raw material component in the preparation method based on theoretical conversion. In the present invention, each oxide is calculated in the most stable oxide form.

[0116] For example, the Fe oxide in the Fe-based catalyst is Fe3O4, and other oxides may be Co3O4, MnO2, MgO, CuO, ZnO, ZrO2, In2O3, BaO, La2O3, CeO2, TiO2, and SiO2.

[0117] If the CuZr oxides in the CuZr-based catalyst are CuO and ZrO2, the second metal oxide may be MnO2, MgO, ZnO, or Al2O3.

[0118] The preparation method of the composite oxide catalyst of the present invention comprises the following steps:

[0119] a1) dispersing the first support, the Fe-based catalyst and the CuZr-based catalyst in water or an organic solvent;

[0120] a2) removing the liquid from the solution A to obtain a solid mixture;

[0121] a3) drying and calcining the solid mixture to obtain the composite oxide catalyst.

[0122] For the two raw materials of Fe-based catalyst and CuZr-based catalyst used in this application, as long as they meet the following requirements: based on the mass of the Fe-based catalyst, the content of Fe oxide is 15wt% to 75wt%, and the content of other oxides is 25wt% to 85wt%; based on the mass of the CuZr-based catalyst, the content of CuZr oxide is 20wt% to 85wt%, and the content of the second metal oxide is 15wt% to 80wt%.

[0123] In the following specific examples, this application provides six specific Fe-based catalysts and their preparation methods. The Fe-based catalysts include A1, A2, A3, A4, A5 and A6, and the preparation methods of A1, A2, A3, A4, A5 and A6 are as follows.

[0124] In one preparation method of A1, the following steps are included: 0.1 mol Fe(NO3)3·9H2O, 0.2 mol Co(NO3)2·6H2O, and 0.5 mol Mg(NO3)2·6H2O are mixed into a 5 mol / L salt solution; NaOH and Na2CO3 are mixed into a 0.2 mol / L precipitant solution in a ratio of 1:2; 5 g of a TiO2 carrier is added to a beaker containing 200 mL of deionized water and heated to 100°C with stirring. The mixed salt solution and the precipitant aqueous solution are dripped into a 100°C beaker in parallel to carry out a precipitation reaction until no more precipitation is produced. The pH is controlled at approximately 12. After the dripping is completed, the mixture is aged at 100°C for 2 hours, then centrifuged, washed, and dried at 120°C. The solid product is calcined at 600°C for 5 hours to obtain the Fe-based catalyst A1. In the calcined A1, based on the mass of A1, the content of Fe oxide was 15.8 wt %, and the content of other oxides was 84.2 wt %.

[0125] In one preparation method of A2, the following steps are included: 0.5 mol Fe(NO3)3·9H2O, 0.1 mol Mn(NO3)2·4H2O, and 0.1 mol Cu(NO3)2·3H2O are mixed into a salt solution with a concentration of 0.5 mol / L, NH3·H2O is mixed into a precipitant solution with a concentration of 5 mol / L, and the solution is heated to 30°C. The mixed salt solution and the precipitant aqueous solution are dripped into a 30°C beaker in parallel to carry out a precipitation reaction until no more precipitation is produced. The pH is controlled at about 7.5. After the dripping is completed, the mixture is aged at 30°C for 48 hours, then centrifuged, washed, and dried at 120°C. The solid product is calcined at 300°C for 24 hours to obtain an alkali metal-free Fe-based catalyst. 5 g of the calcined alkali-metal-free Fe-based catalyst was impregnated with an equal volume of 0.1 g of KNO3. The K salt was then loaded onto the catalyst by impregnation. The catalyst was then dried at 120°C for 24 hours and calcined at 300°C for 24 hours to obtain Fe-based catalyst A2. The calcined catalyst A2 had an Fe oxide content of 71 wt% and other oxides of 29 wt%, based on the mass of A2.

[0126] One method for preparing A3 includes the following steps: preparing a 3 mol / L salt solution of 0.2 mol Fe(NO3)3·9H2O, 0.2 mol Co(NO3)2·6H2O, 0.1 mol Zn(NO3)3·6H2O, and 0.05 mol In(NO3)3; and heating the solution to 60°C by adding KOH and K2CO3 in a 1:2 ratio to form a 3 mol / L precipitant solution. The solution is then dripped into a 60°C beaker in parallel to allow precipitation to proceed until no further precipitation occurs. The pH is maintained at approximately 9.5. After the addition is complete, the mixture is aged at 60°C for 4 hours, followed by centrifugation, washing, and drying at 120°C. The solid product is calcined at 500°C for 10 hours to obtain Fe-based catalyst A3. The calcined A3 has an Fe oxide content of 37.6 wt% and other oxides of 62.4 wt%, based on the mass of A3.

[0127] In one preparation method of A4, the following steps are included: 0.2 mol Fe(NO3)3·9H2O, 0.1 mol Co(NO3)2·6H2O, and 0.1 mol Zn(NO3)3·6H2O are mixed into a 1 mol / L salt solution; NaOH and Na2CO3 are mixed into a 2 mol / L precipitant solution in a 1:2 ratio; and the solution is heated to 80°C. The mixed salt solution and the precipitant aqueous solution are dripped into an 80°C beaker in parallel to carry out a precipitation reaction until no more precipitation is produced. The pH is controlled at approximately 9.5. After the dripping is completed, the catalyst is aged at 80°C for 2 hours, then centrifuged, washed, and dried at 120°C. The solid product is calcined at 350°C for 5 hours to obtain Fe-based catalyst A4. In the calcined A4, the Fe oxide content is 48.8 wt% and the content of other oxides is 51.2 wt%, based on the mass of A4.

[0128] In one preparation method of A5, the following steps are included: 0.3 mol Fe(NO3)3·9H2O, 0.3 mol Co(NO3)2·6H2O, 0.1 mol Zr(NO3)4·5H2O, and 0.05 mol La(NO3)3 are mixed into a 3 mol / L salt solution, (NH4)2CO3 is mixed into a 5 mol / L precipitant solution, and the solution is heated to 60°C. 5 g of SiO2 carrier is added to a beaker containing 50 mL of deionized water and heated to 60°C with stirring. The mixed salt solution and precipitant aqueous solution are dripped into a 60°C beaker in parallel to carry out a precipitation reaction until no more precipitation is produced. The pH is controlled at approximately 10. After the dripping is completed, the mixture is aged at 60°C for 24 hours, then centrifuged, washed, and dried at 120°C. The solid product is calcined at 400°C for 8 hours to obtain an alkali-metal-free Fe-based catalyst. 5 g of the calcined alkali-metal-free Fe-based catalyst was impregnated with an equal volume of 0.1 g of NaCO. The Na salt was then loaded by impregnation. The catalyst was then dried at 120°C for 24 hours and calcined at 400°C for 4 hours to obtain Fe-based catalyst A5. The calcined catalyst A5 had an Fe oxide content of 30.5 wt% and other oxides of 69.5 wt%, based on the mass of A5.

[0129] In one preparation method of A6, the following steps are included: 0.5 mol Fe(NO3)3·9H2O, 0.1 mol Co(NO3)2·6H2O, 0.01 mol Ba(NO3)2, and 0.1 mol Ce(NO3)3·6H2O are mixed into a 2 mol / L salt solution, NaOH and Na2CO3 are mixed into a 2 mol / L precipitant solution in a ratio of 1:2, and the solution is heated to 80°C. The mixed salt solution and the precipitant aqueous solution are dripped into a 60°C beaker in parallel to carry out a precipitation reaction until no more precipitation is produced. The pH is controlled at about 8.5. After the dripping is completed, the mixture is aged at 80°C for 10 hours, then centrifuged, washed, and dried at 120°C. The solid product is calcined at 500°C for 8 hours to obtain an alkali metal-free Fe-based catalyst. 5 g of the calcined alkali-metal-free Fe-based catalyst was impregnated with an equal volume of 0.1 g of CsNO3 to load the Cs salt. The catalyst was then dried at 120°C for 24 hours and calcined at 400°C for 4 hours to obtain Fe-based catalyst A6. The calcined catalyst A6 had an Fe oxide content of 59 wt% and other oxides of 41 wt%, based on the mass of A6.

[0130] In the following examples, the present application provides four specific CuZr-based catalysts and their preparation methods. The CuZr-based catalysts include B1, B2, B3, and B4, and the preparation methods of B1, B2, B3, and B4 are as follows.

[0131] One method for preparing B1 includes the following steps: preparing a mixed solution of 2 mol Cu(NO3)2·3H2O, 0.1 mol Zr(NO3)4·5H2O, and 0.5 mol Zn(NO3)2·6H2O to form a total metal concentration of 0.5 mol / L; then dissolving KOH and K2CO3 in a certain amount of deionized water to form an alkaline solution with a concentration of 0.5 mol / L. The mother liquor is added to a beaker, the addition temperature is adjusted to 30°C, and the pH of the solution is controlled to 10. The two solutions are co-precipitated into the stirred mother liquor in parallel until no more precipitation occurs. After the addition is completed, the mixture is aged at 30°C for 48 hours, centrifuged and washed, and then dried in a 150°C oven for 36 hours. The mixture is then transferred to a muffle furnace and calcined at a programmed temperature of 600°C for 2 hours. After calcination, catalyst B1 is obtained. Based on the mass of B1, the CuZr oxide content is 81 wt%, and the second metal oxide content is 19 wt%.

[0132] One method for preparing B2 includes the following steps: preparing a mixed solution with a total metal concentration of 5 mol / L by combining 0.1 mol Cu(NO3)3·3H2O, 0.007 mol Zr(NO3)4·5H2O, and 0.4 mol Mn(NO3)2·4H2O; then dissolving (NH4)2CO3 in a certain amount of deionized water to form an alkaline solution with a concentration of 5 mol / L. The mother liquor is added to a beaker, the addition temperature is adjusted to 65°C, and the pH of the solution is controlled to 12. The two solutions are then co-precipitated into the stirred mother liquor in parallel until no further precipitation occurs. After the addition is complete, the mixture is aged at 65°C for 15 hours, centrifuged and washed, dried in a 100°C oven for 12 hours, and then transferred to a muffle furnace and programmed to 450°C for calcination for 4 hours. After calcination, catalyst B2 is obtained. Based on the mass of B2, the content of CuZr oxide is 20.2 wt %, and the content of the second metal oxide is 79.8 wt %.

[0133] One method for preparing B3 includes the following steps: preparing a mixed solution with a total metal concentration of 2 mol / L by combining 0.6 mol Cu(NO3)3·3H2O, 0.06 mol Zr(NO3)4·5H2O, 0.3 mol Zn(NO3)2·6H2O, and 0.1 mol Al(NO3)3·9H2O; dissolving NaOH and Na2CO3 in deionized water to prepare a 2 mol / L solution; adding the two solutions to a beaker containing deionized water; controlling the pH to approximately 9 at 80°C until no precipitation occurs; stirring at 80°C for 3 hours; filtering and washing with deionized water; and drying the resulting product at 100°C. Finally, calcining the dried product in a muffle furnace at 550°C for 8 hours to obtain catalyst B3. Based on the mass of B3, the CuZr oxide content is 65.25 wt%, and the second metal oxide content is 34.75 wt%.

[0134] One method for preparing B4 includes the following steps: preparing a mixed solution of 0.6 mol CuCl2·2H2O, 0.1 mol Zr(NO3)4·5H2O, 0.2 mol Mg(NO3)2·6H2O, and 0.2 mol Al(NO3)3·9H2O to a total metal concentration of 1 mol / L; then dissolving KOH and K2CO3 in a certain amount of deionized water to form an alkaline solution with a concentration of 1 mol / L. The mother liquor is added to a beaker, the addition temperature is adjusted to 65°C, and the pH is controlled to approximately 10. The two solutions are then co-precipitated into the stirred mother liquor in parallel until no further precipitation occurs. After the addition is complete, the mixture is aged at 65°C for 15 hours, centrifuged and washed, dried in a 100°C oven for 12 hours, and then transferred to a muffle furnace and calcined at 300°C for 24 hours. After calcination, catalyst B4 is obtained. Based on the mass of B4, the content of CuZr oxide is 67.9 wt %, and the content of the second metal oxide is 32.1 wt %.

[0135] In a specific embodiment, the composite oxide catalyst is pressed into pellets, crushed, and then loaded into a fixed bed reactor for reaction.

[0136] It should be noted that the amount of the composite oxide catalyst used can be adjusted according to the catalytically effective amount of the specific catalyst, reaction conditions, convenience and economy of actual operation, and stability of long-term operation.

[0137] Example 1

[0138] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw materials, the Fe-based catalyst content is 75 wt%, the CuZr-based catalyst content is 24 wt%, and the first carrier content is 1 wt%. The Fe-based catalyst is A1; the CuZr-based catalyst is B1; and the first carrier is SiO2.

[0139] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0140] 1) Add 250 mL of ethanol to a beaker. While stirring, add 0.1 g of fumed SiO2 to the beaker. Stir thoroughly at room temperature for 30 minutes. Then add 7.5 g of Al and continue stirring for 30 minutes. Finally, add 2.4 g of B1 and stir for 2 hours to form solution A.

[0141] 2) removing ethanol from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0142] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 250° C. for 10 h to obtain the composite oxide catalyst.

[0143] This embodiment also provides a use of a composite oxide catalyst in the production of ethanol by hydrogenation of carbon dioxide.

[0144] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size and then loaded into a fixed bed reactor for reduction and carbonization. Pure H2 was used as the reducing gas, and the reduction space velocity was 30,000 h-1. -1 , the reduction temperature is 500℃, and the reduction time is 2h. After the reduction process is completed, the temperature is lowered to 200℃, and then the synthesis gas is switched to H2 / CO=1, and the temperature is kept at 30000h. -1 After carbonization, the temperature was lowered to 80°C, and a reaction gas of H2 / CO2=3 was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 8.0 MPa, and the reaction temperature was adjusted to 260°C and the reaction space velocity was 2000 h-1. -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0145] Example 2

[0146] This embodiment provides a composite oxide catalyst. The composite oxide catalyst raw material includes an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw material, the Fe-based catalyst content is 40 wt%, the CuZr-based catalyst content is 55 wt%, and the first carrier content is 5 wt%. The Fe-based catalyst is A2; the CuZr-based catalyst is B2; and the first carrier is Al2O3.

[0147] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0148] 1) Add 250 mL of methanol to a beaker. While stirring, add 0.5 g of gaseous Al2O3 to the beaker. Stir thoroughly at room temperature for 30 minutes. Then add 4.0 g of A2 and continue stirring for 30 minutes. Finally, add 5.5 g of B2 and stir for 1 hour to form solution A.

[0149] 2) removing methanol from solution A by rotary evaporation at 100° C. to obtain a solid mixture;

[0150] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 400° C. for 5 h to obtain the composite oxide catalyst.

[0151] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size and then loaded into a fixed bed reactor for reduction and carbonization. The reducing gas was a mixture of H2 and N2, with an H2 content of 10% by volume and a reduction space velocity of 2000 h / min. -1 , the reduction temperature is 300℃, and the reduction time is 24h. After the reduction process is completed, the temperature is raised to 320℃, and the mixture of CO and Ar with a volume ratio of 1:1 is switched to 3000h -1 After carbonization, the temperature was lowered to 100°C, and H2 / CO2=3 reaction gas was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 8.0 MPa, and the reaction temperature was adjusted to 320°C and the reaction space velocity was 20000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0152] Example 3

[0153] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw materials, the Fe-based catalyst content is 48 wt%, the CuZr-based catalyst content is 49.9 wt%, and the first carrier content is 2.1 wt%. The Fe-based catalyst is A3; the CuZr-based catalyst is B3; and the first carrier is SiO2.

[0154] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0155] 1) Add 250 mL of ethanol to a beaker. While stirring, add 0.6 g of liquid silica sol (SiO2 content 35 wt%) to the beaker. Stir thoroughly at room temperature for 30 minutes. Then add 4.8 g of A3. Stir for another 30 minutes. Finally, add 4.99 g of B3. Stir for 2 hours to form solution A.

[0156] 2) removing ethanol from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0157] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 500° C. for 2 h to obtain the composite oxide catalyst.

[0158] This embodiment also provides a use of a composite oxide catalyst in the production of ethanol by hydrogenation of carbon dioxide.

[0159] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size and then loaded into a fixed bed reactor for reduction and carbonization. Pure H2 was used as the reducing gas, and the reduction space velocity was 10,000 h-1. -1 , the reduction temperature is 400℃, and the reduction time is 6h. After the reduction process is completed, the temperature is lowered to 320℃, and then switched to a mixed gas with a volume ratio of 1:1 between synthesis gas and Ar, wherein H2 / CO=1, and the mixture is heated for 10000h. -1 After carbonization, the temperature was lowered to 100°C, and H2 / CO2=3 reaction gas was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 6.0 MPa, and the reaction temperature was adjusted to 320°C and the reaction space velocity was 6000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0160] Example 4

[0161] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw materials, the Fe-based catalyst content is 67 wt%, the CuZr-based catalyst content is 30 wt%, and the first carrier content is 3 wt%. The Fe-based catalyst is A4; the CuZr-based catalyst is B4; and the first carrier is TiO2.

[0162] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0163] 1) Add 250 mL of acetone to a beaker. While stirring, add 0.3 g of TiO2 aerosol to the beaker. Stir thoroughly at room temperature for 30 minutes. Then add 6.7 g of A4 and continue stirring for 30 minutes. Finally, add 3.0 g of B4 and stir for 5 hours to form solution A.

[0164] 2) removing acetone from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0165] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 450° C. for 4 h to obtain the composite oxide catalyst.

[0166] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into a fixed bed reactor for reduction and carbonization. The reducing gas was a mixture of CO and N2, with a CO content of 10% by volume and a reduction space velocity of 20,000 h / min. -1 , the reduction temperature is 300℃, and the reduction time is 12h. After the reduction process is completed, switch to a mixed gas with a volume ratio of 1:1 between synthesis gas and Ar, where H2 / CO=1, and the reaction temperature is 300℃ and the reduction time is 12h. -1 After carbonization, the temperature was lowered to 100°C, and H2 / CO2=1 reaction gas was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 4.0 MPa, and the reaction temperature was adjusted to 340°C and the reaction space velocity was 10000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0167] Example 5

[0168] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw materials, the Fe-based catalyst content is 75 wt%, the CuZr-based catalyst content is 23.6 wt%, and the first carrier content is 1.4 wt%. The Fe-based catalyst is A5; the CuZr-based catalyst is B3; and the first carrier is SiO2.

[0169] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0170] 1) Add 250 mL of ethanol to a beaker. While stirring, add 0.4 g of liquid silica sol (SiO2 content 35 wt%) to the beaker. Stir thoroughly at room temperature for 30 minutes. Then add 7.5 g of A5. Stir for another 30 minutes. Finally, add 2.36 g of B3. Stir for 5 hours to form Solution A.

[0171] 2) removing ethanol from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0172] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 350° C. for 10 h to obtain the composite oxide catalyst.

[0173] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into a fixed bed reactor for reduction and carbonization. Pure H2 was used as the reducing gas, and the reduction space velocity was 8000 h / min. -1 , the reduction temperature is 400℃, and the reduction time is 5h. After the reduction process is completed, switch to synthesis gas, in which H2 / CO=1, and the temperature is 400℃ and the reduction time is 5h. -1 After carbonization, the temperature was lowered to 220°C, and a reaction gas of H2 / CO2=5 was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 10.0 MPa, and the reaction temperature was adjusted to 260°C and the reaction space velocity was 1000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0174] Example 6

[0175] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw materials, the Fe-based catalyst content is 50 wt%, the CuZr-based catalyst content is 49 wt%, and the first carrier content is 1 wt%. The Fe-based catalyst is A6; the CuZr-based catalyst is B1; and the first carrier is SiO2.

[0176] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0177] 1) Add 250 mL of water to a beaker. While stirring, add 0.1 g of fumed SiO2 to the beaker. Stir thoroughly at room temperature for 30 minutes. Then, add 5.0 g of A6 and continue stirring for 30 minutes. Finally, add 4.9 g of B2 and stir for 5 hours to form solution A.

[0178] 2) removing water from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0179] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 400° C. for 5 h to obtain the composite oxide catalyst.

[0180] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into a fixed bed reactor for reduction and carbonization. The reducing gas was a mixture of H2 and N2, with a volume content of H2 of 50% and a reduction space velocity of 6000 h / min. -1 , the reduction temperature is 350℃, and the reduction time is 8h. After the reduction process is completed, switch to a mixed gas with a volume ratio of CO and Ar of 1:9, and heat for 6000h -1 After carbonization, the temperature was adjusted to 280°C, and a reaction gas of H2 / CO2=3 was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 5.0 MPa, and the reaction space velocity was 6000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0181] Example 7

[0182] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the composite oxide catalyst raw materials, the Fe-based catalyst content is 35 wt%, the CuZr-based catalyst content is 62 wt%, and the first carrier content is 3 wt%. The Fe-based catalyst is A4; the CuZr-based catalyst is B2; and the first carrier is TiO2.

[0183] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0184] 1) Add 250 mL of water to a beaker. While stirring, add 0.3 g of fumed TiO2 to the beaker. Stir thoroughly at room temperature for 30 minutes. Then, add 3.5 g of A4 and continue stirring for 30 minutes. Finally, add 6.2 g of B2 and stir for 5 hours to form solution A.

[0185] 2) removing water from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0186] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 400° C. for 4 h to obtain the composite oxide catalyst.

[0187] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size and then loaded into a fixed bed reactor for reduction and carbonization. The reducing gas was a mixture of H2 and N2, with a volume content of H2 of 50% and a reduction space velocity of 10,000 h / min. -1 , the reduction temperature is 250℃, and the reduction time is 32h. After the reduction process is completed, it is switched to synthesis gas, in which H2 / CO=1, and the temperature is 10000h. -1 After carbonization, the reaction gas of H2 / CO2=2 was introduced for 30 min, and then the back pressure of the same reaction gas was increased to 6.0 MPa, and the reaction temperature was adjusted to 320°C and the reaction space velocity was 3000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0188] Example 8

[0189] This embodiment provides a composite oxide catalyst. The raw materials for the composite oxide catalyst include an Fe-based catalyst, a CuZr-based catalyst, and a first carrier. Based on the total mass of the raw materials for the composite oxide catalyst, the Fe-based catalyst content is 55 wt%, the CuZr-based catalyst content is 41 wt%, and the first carrier content is 4 wt%. The Fe-based catalyst is A4; the CuZr-based catalyst is B3; and the first carrier is SiO2.

[0190] This embodiment also provides a method for preparing a composite oxide catalyst, which comprises the following steps:

[0191] 1) Add 250 mL of water to a beaker. While stirring, add 0.4 g of fumed SiO2 to the beaker. Stir thoroughly at room temperature for 30 minutes. Then, add 5.5 g of A4 catalyst. Continue stirring for 30 minutes. Finally, add 4.1 g of B3 and stir for 5 hours to form solution A.

[0192] 2) removing water from solution A by rotary evaporation at 80° C. to obtain a solid mixture;

[0193] 3) The solid mixture was dried at 120° C. for 12 h, and then calcined at 400° C. for 4 h to obtain the composite oxide catalyst.

[0194] The composite oxide catalyst described in this example was pelletized and crushed to 40-60 mesh. 1.0 g of the crushed composite oxide catalyst was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into a fixed bed reactor for reduction and carbonization. H2 was used as the reducing gas, and the reduction space velocity was 8000 h-1. -1 , the reduction temperature is 350℃, and the reduction time is 12h. After the reduction process is completed, it is switched to synthesis gas, in which H2 / CO=0.2, and the temperature is 8000h. -1 After carbonization, the temperature was lowered to 280°C, and H2 / CO2=3 reaction gas was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 8.0 MPa, and the reaction temperature was adjusted to 300°C and the reaction space velocity was 6000 h -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0195] Comparative Example 1

[0196] Catalyst A1 was tableted and crushed to 40-60 mesh. 1.0 g of the crushed catalyst A1 was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into a fixed bed reactor for reduction and carbonization. Pure H2 was used as the reducing gas, and the reduction space velocity was 10,000 h -1 , the reduction temperature is 400℃, and the reduction time is 2h. After the reduction process is completed, the temperature is lowered to 200℃, and then the synthesis gas is switched to H2 / CO=1 for 10000h -1 After carbonization, the temperature was lowered to 80°C, and a reaction gas of H2 / CO2=3 was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 8.0 MPa, and the reaction temperature was adjusted to 320°C and the reaction space velocity was 6000 h-1. -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0197] Comparative Example 2

[0198] Catalyst B3 was tableted and crushed to 40-60 mesh. 1.0 g of the crushed catalyst B3 was mixed with 3.0 g of quartz sand of the same mesh size, and then loaded into a fixed bed reactor for reduction and carbonization. Pure H2 was used as the reducing gas, and the reduction space velocity was 10,000 h -1 , the reduction temperature is 400℃, and the reduction time is 2h. After the reduction process is completed, the temperature is lowered to 200℃, and then the synthesis gas is switched to H2 / CO=1 for 10000h -1 After carbonization, the temperature was lowered to 80°C, and a reaction gas of H2 / CO2=3 was introduced for 30 minutes. Then, the back pressure of the same reaction gas was increased to 8.0 MPa, and the reaction temperature was adjusted to 320°C and the reaction space velocity was 6000 h-1. -1 After the reaction, the types and contents of the various components in the product were analyzed using gas chromatography (Agilent 8860), and the conversion rate and selectivity of the reaction were calculated accordingly. The specific results are shown in Table 1.

[0199] Table 1 Example catalytic reaction results

[0200]

[0201] As shown in Table 1, the composite oxide catalysts described herein exhibit high activity and high ethanol selectivity in the reaction of hydrogenating carbon dioxide to ethanol. Under certain synthesis conditions, the composite oxide catalysts described in the Examples of this application all exhibited ethanol selectivity exceeding 85%, significantly superior to the catalytic performance of the single Fe-based catalysts or the single CuZr-based catalysts in Comparative Examples 1 and 2.

[0202] In summary, the composite oxide catalyst of the present invention has the characteristics of simple preparation, low cost, easy repeatability and good stability; the composite oxide catalyst can be used for carbon dioxide hydrogenation to ethanol, and exhibits excellent catalytic performance, achieving high ethanol selectivity under conditions of high single-pass CO2 conversion rate. For example, when the single-pass CO2 conversion rate is 80.2%, the ethanol selectivity can reach 93.9%.

[0203] The present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0204] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A composite oxide catalyst, characterized in that The raw materials of the composite oxide catalyst include Fe-based catalyst, CuZr-based catalyst and a first carrier; Based on the total mass of the raw materials of the composite oxide catalyst, the content of the Fe-based catalyst is 20wt% to 80wt%, the content of the CuZr-based catalyst is 15wt% to 79wt%, and the content of the first carrier is 1wt% to 5wt%.

2. The composite oxide catalyst according to claim 1, characterized in that The Fe-based catalyst comprises Fe oxide and other oxides, and based on the mass of the Fe-based catalyst, the content of the Fe oxide is 15wt% to 75wt%, and the content of the other oxides is 25wt% to 85wt%, and the other oxides comprise a first metal oxide, and the first metal is selected from one or more of alkali metals, alkaline earth metals, transition metals, rare earth metals and Group IIIA metals; And or, the CuZr-based catalyst comprises CuZr oxide and a second metal oxide, the CuZr oxide is based on the mass of the CuZr-based catalyst, the content of the CuZr oxide is 20wt% to 85wt%, the content of the second metal oxide is 15wt% to 80wt%, and the second metal is selected from one or more of Zn, Al, Mg, and Mn; And / or, the first carrier is selected from one or more of SiO2, TiO2, Al2O3.

3. The composite oxide catalyst according to claim 2, characterized in that The preparation method of the Fe-based catalyst comprises: b1) mixing the Fe oxide and a soluble salt of the first metal oxide other than an alkali metal and dissolving them in water to obtain a solution B; b2) dissolving the precipitant in water to obtain solution C; b3) dropping the solution B and the solution C into the mother solution simultaneously for co-precipitation until no precipitation is generated; b4) after the coprecipitation is completed, aging is performed to obtain a solution D; b5) subjecting the solution D to solid-liquid separation, washing, drying and calcining the solid product obtained by the solid-liquid separation to obtain the Fe-based catalyst; And / or, the preparation method of the CuZr-based catalyst comprises the following steps: c1) mixing the CuZr oxide and the soluble salt of the second metal oxide and dissolving them in water to obtain a solution E; c2) dissolving the precipitant in water to obtain a solution F; c3) dropping the solution F and the solution E into the mother solution simultaneously for co-precipitation until no precipitation is generated; c4) after the coprecipitation is completed, aging is performed to obtain solution G; c5) performing solid-liquid separation on the solution G, washing, drying and calcining the obtained solid product to obtain the CuZr-based catalyst; and / or, the other oxide further comprises a second carrier, the second carrier is selected from one or more of SiO2, TiO2, Al2O3; and / or, the alkali metal is selected from one or more of Li, Na, K, Rb and Cs; And / or, the alkaline earth metal is selected from one or more of Mg, Ca and Ba; And / or, the transition metal is selected from one or more of Mn, Co, Zr, Cu and Zn; And / or, the rare earth metal is selected from one or both of La and Ce; And / or, the IIIA group metal is selected from one or both of Al and In; And / or, the molar ratio of Cu to Zr in the CuZr oxide is (5-20):

1.

4. The composite oxide catalyst according to claim 3, characterized in that In the step b3), a second carrier is also dispersed in the mother liquid; And / or, in step b1), the molar concentration of solution B is 0.1 to 5 mol / L; And / or, in step b2), the concentration of solution C is 0.1 to 5 mol / L; And / or, in step b2), the precipitant is selected from one or more of Na2CO3, K2CO3, (NH4)2CO3, NaOH, KOH and NH3·H2O; And / or, in the step b3), the coprecipitation temperature is 30 to 100°C; And / or, in the step b3), the mother liquor is water; And / or, in the step b3), the pH of the mother liquor during the coprecipitation process is 7 to 12; And / or, in the step b4), the aging temperature is 30-100°C; And / or, in the step b4), the aging time is 2 to 48 hours; And / or, in the step b5), the calcination temperature is 300-600°C; And / or, in the step b5), the calcination time is 2 to 24 hours; And / or, the step b5) further comprises impregnation, wherein the impregnation solution is an aqueous solution of a soluble salt of the alkali metal, and the operation of the step b5) is repeated after the impregnation, wherein the concentration of the aqueous solution of the soluble salt of the alkali metal is 0.1 to 5 mol / L; And / or, in step c1), the molar concentration of the solution E is 0.1 to 5 mol / L; And / or, in step c2), the concentration of the solution F is 0.1 to 5 mol / L; And / or, in step c2), the precipitant is selected from one or more of Na2CO3, K2CO3, (NH4)2CO3, NaOH, KOH and NH3·H2O; And / or, in step c3), the mother liquor is water; And / or, in the step c3), the coprecipitation temperature is 30-100°C; And / or, in the step c3), the pH of the mother liquor during the coprecipitation process is 7 to 12; And / or, in the step c4), the aging temperature is 30-100°C; And / or, in the step c4), the aging time is 2 to 48 hours; And / or, in the step c5), the calcination temperature is 300-600°C; And / or, in the step c5), the calcination time is 2 to 24 hours.

5. The method for preparing a composite oxide catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: a1) mixing the first carrier, the Fe-based catalyst and the CuZr-based catalyst to obtain a solid mixture; a2) calcining the solid mixture to obtain the composite oxide catalyst.

6. The preparation method according to claim 5, characterized in that: In the step a2), the calcination temperature is 200 to 500° C.; and / or, in the step a2), the calcination time is 2 to 10 hours.

7. Use of the composite oxide catalyst according to any one of claims 1 to 4 in the preparation of ethanol by hydrogenation of carbon dioxide, characterized in that: Before the composite oxide catalyst is used for preparing ethanol by hydrogenating carbon dioxide, the catalyst is first subjected to reduction treatment and carbonization treatment in sequence.

8. The use according to claim 7, characterized in that The gas used in the reduction treatment is selected from one or more of H2, CO, synthesis gas and inert gas; And / or, the temperature of the reduction treatment is 200-500°C; And / or, the reduction treatment time is 2 to 48 hours; And / or, the space velocity of the reduction treatment is 1000~30000h -1 ; And / or, the gas used in the carbonization treatment is selected from one or more of CO, synthesis gas and inert gas; And / or, the space velocity of carbonization treatment is 1000~30000h -1 ; And / or, the temperature of the carbonization treatment is 200-400°C; And / or, the carbonization treatment time is 5 to 48 hours.

9. A method for preparing ethanol using the composite oxide catalyst according to any one of claims 1 to 4, characterized in that: CO2 and H2 react under the catalytic action of the composite oxide catalyst to produce ethanol.

10. The method according to claim 9, characterized in that The volume ratio of H2 to CO2 is (0.5-5):1; And / or, the reaction temperature is 200-400°C; And / or, the reaction space velocity is 1000~20000h -1 ; And / or, the reaction pressure is 3-10 MPa.

Citation Information

Patent Citations

  • Nano-gold catalysts for the synthesis of ethanol from carbon dioxide and their preparation methods

    CN106582627B

  • Preparation methods and applications of cobalt-based catalysts for catalytic production of ethanol from carbon dioxide

    CN108380216B

  • Pd-based catalysts supported on composite oxides, their preparation methods and applications

    CN110102294B

  • Preparation of supported gold catalyst, and application of supported gold catalyst in ethanol preparation through carbon dioxide hydrogenation

    CN111185160A

  • Porous copper-based catalyst for preparing ethanol through carbon dioxide hydrogenation and preparation method thereof

    CN113751062A